Improving the Lifetime of CsPbBr3 Perovskite in Water Using Self-Healing and Transparent Elastic Polymer Matrix - Laysandra, Livy; Fan, Yong Jie; Adena, Cecilia; Lee, Yen-Ting; Au-Duong, Ai-Nhan; Chen, Liang-Yih; Chiu, Yu-Cheng (Frontiers in Chemistry, 2020)
This study developed a simple and efficient strategy to stabilize inorganic halide perovskite CsPbX3 at high relative humidity by embedding it into the matrix with elastic and self-healing features. The polymer matrix has a naturally hydrophobic characteristic of n-butyl acrylate segment (n-BA) and cross-linkable and healable moiety from N-(hydroxymethyl) acrylamide segment (NMA). It was chosen due to the provisions of both a surrounding protective layer for inorganic perovskite and elastic, as well as healing ability to the whole organic-inorganic composite. This fabricated CsPbBr3/PBA-co-PNMA composite was demonstrated to stably persist against the suffering from hydrolysis of perovskites when exposed to a high moisture environment. The PL intensity of the composite after crosslinking was found to be relatively stable after 30 days of exposure to air. Upon water immersion, the PL intensity of composite only showed a decrease of 32% after the first 6 h, then remained stable for 6 h afterward. Furthermore, this fabricated composite was not only flexible and relatively transparent but also exhibited excellent self-healing capability in ambient conditions (T = 25°C), in which the self-healing efficiency after 24 h was above 40%. The tensile strength and stretching ability of 5 wt% perovskite content in the random copolymer were observed to be 3.8 MPa and 553.5% respectively. Overall, flexible and self-healing properties combining with high luminescence characteristics are very promising materials for next-generation soft optical devices.